Critical appraisal of reporting randomized clinical trials published in Iranian dental journals during 2003-2010. - Raha Habib Agahi; Nader Navabi; Arash Shahravan; Amirreza Ghassemi (Tehran University of Medical Sciences, 2014)
Considering the importance of randomized clinical trials (RCTs) in the evidence-based approach, the objective of this study was critical appraisal of reporting RCTs in Iranian dental journals.After adequate searching, 113 RCT articles published during 2003-2010 were reviewed for quality of reporting with the CONSORT scale. The quality of each paper was assessed on 20.Although statistical analysis was described in 93.8%, acceptable methods for randomization and blinding were found in only 8% and 11.5% of the papers, respectively. Reasons for withdrawal were also given in just 20.4% of the articles.This study revealed that the quality of reporting RCTs in Iranian dental journals does not meet the recommended standards generally and needs to be improved.